DEVELOPMENT OF A COOLING LOAD PREDICTION MODEL FOR OFFICE BUILDINGS OF BAYERO UNIVERSITY KANO - HARUNA, IBRAHIM USMAN; RUFAI, IBRAHIM AHMAD; YAHAYA, DALHATU BALARABE (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Overestimation of building cooling load results into an oversized cooling system with consequent waste of energy. Conversely, thermal comfort would be sacrificed if the building cooling load is underestimated because of the use of undersized cooling system. The computer-based methods for cooling load calculation are costly while most of the inverse models are complex and require enough time to train the models. In this paper, a simplified multiple linear regression model was developed using the concept of Taguchi orthogonal array. The model developed has high performance based on the computed ????2 and variance inflation factor. The prediction model developed was validated using resampling technique and the consistency in the root mean squared error (RMSE) in all the holdout samples indicates the high accuracy of the model developed. The proposed model has high inference and prediction powers and could be used for predicting cooling load of office buildings of Bayero University Kano (BUK) or any building with similar characteristics.